Point of Care Perioperative Coagulation Management in Liver Transplantation and Complete Portal Vein Thrombosis - Cristiano Piangatelli; Lucia Faloia; Claudia Cristiani; Ilaria Valentini; Marco Vivarelli (Case Reports in Transplantation)
Liver transplantation (LT) is a serious hemostatic challenge in patients with portal vein thrombosis (PVT). Advances in monitoring systems have improved surgery in this setting. We report the successful application of a point-of-care (POC) rotational viscoelastic thromboelastometry-guided (TEM) testing system (ROTEM) which allowed management of coagulation during LT in a 64-year-old cirrhotic patient with a model for end-stage liver disease (MELD) score of 16. Perioperatively, the patient showed complete PVT, hepatomegaly, splenomegaly, recanalization of the umbilical vein, and portosystemic shunt. Macroscopic liver and spleen adherences with collateral circulation were evident. Coagulation factors and fibrinolysis were assessed preoperatively and at graft reperfusion to evaluate the need of hemostatic therapy. Based on ROTEM findings, the patient received 16 g of human fibrinogen concentrate, half preoperatively (with prothrombin complex concentrate 2000 IU, tranexamic acid 1 g, and platelets 2 IU), and two doses of 4 g before and after graft reperfusion; we achieved normalization of all monitored parameters. No ischemia-reperfusion syndrome was present. Postoperatively portal vein flux at Color-Doppler ultrasonography was normal. After a 3-day ICU stay, the patient was moved to the Department of Surgery and discharged on day 14. The postoperative course was uneventful and did not require any further haemostatic therapy.